2016
DOI: 10.5966/sctm.2015-0411
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Transforming Growth Factor-β Activation Recruits Mesenchymal Stem Cells During Prostatic Hyperplasia

Abstract: Benign prostatic hyperplasia (BPH) is the overgrowth of prostate tissues with high prevalence in older men. BPH pathogenesis is not completely understood, but it is believed to be a result of de novo overgrowth of prostatic stroma. In this study, we show that aberrant activation of transforming growth factor‐β (TGF‐β) mobilizes mesenchymal/stromal stem cells (MSCs) in circulating blood, which are recruited for the prostatic stromal hyperplasia. Elevated levels of active TGF‐β were observed in both a phenylephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 68 publications
(85 reference statements)
1
25
0
Order By: Relevance
“…Based upon these analytical and functional characteristics (Figure ), MSCs have been identified in radical prostatectomy tissue from men with prostate cancer in a systematic analysis of benign and malignant prostate tissue obtained from multiple donors representing different disease states and a wide range of age groups, from fetal development through adult death . Our group and others have demonstrated the in vivo recruitment of MSCs to prostate tissue from systemic sources using a variety of independent techniques, including transgenic chimeras, in vivo cell tracking methodologies, and tissue recombination models . This raises the question of whether MSCs are contributing to prostate cancer progression.…”
Section: Introductionmentioning
confidence: 95%
“…Based upon these analytical and functional characteristics (Figure ), MSCs have been identified in radical prostatectomy tissue from men with prostate cancer in a systematic analysis of benign and malignant prostate tissue obtained from multiple donors representing different disease states and a wide range of age groups, from fetal development through adult death . Our group and others have demonstrated the in vivo recruitment of MSCs to prostate tissue from systemic sources using a variety of independent techniques, including transgenic chimeras, in vivo cell tracking methodologies, and tissue recombination models . This raises the question of whether MSCs are contributing to prostate cancer progression.…”
Section: Introductionmentioning
confidence: 95%
“…Recent evidence suggests the presence of at least 4 different stromal cell types in the prostate (85). The contribution of each of these indigenous cell types to stromal hyperplasia is poorly understood, as is the contribution of mesenchymal stem cells recruited from outside the prostate (86). The different types of prostatic hyperplasia (i.e.…”
Section: Prostate Cell Biology and Anatomymentioning
confidence: 99%
“…TGF‐β is known as the main inducer of CAF/myofibroblast differentiation during reactive stroma development . Different authors also reported that TGF‐β regulates reactive stroma phenotype through angiogenesis induction, promoting vessel formation, tumor growth, and cancer progression .…”
Section: Discussionmentioning
confidence: 99%
“…62 TGF-β is known as the main inducer of CAF/myofibroblast differentiation during reactive stroma development. 15,82 Different authors also reported that TGF-β regulates reactive stroma phenotype through angiogenesis induction, promoting vessel formation, tumor growth, and cancer progression. 16,83,84 Thus, we hypothesized that an angiokinase inhibitor, such as nintedanib, would hamper TGF-β actions during stromal reaction.…”
Section: Discussionmentioning
confidence: 99%